Nutritive value, methane production and energy efficiency for animal functions of dual purpose sorghum hybrids - Singh, Sultan; Gehrana, Deepika; Shukla, G P (The Indian Journal of Animal Sciences, 2012)
Dual purpose sorghum hybrids (20) were developed using 8 male sterile lines and 18 advanced breeding selected lines. Hybrids were grown under similar agronomic and soil conditions and evaluated for their nutritional composition, palatability attributes and energetic efficiency for animal production. Mean CP contents of hybrids were 9.50%, ranging from 12.0% (673A × EC 507815) to 7.2% (673A × CSV 15). Cell wall polysaccharides (NDF, ADF and cellulose) varied from 55.71–70.53, 31.84–42.88 and 25.43–33.32%, respectively, across the hybrids. Mean EE and lignin contents were 1.40 and 4.73% in the evaluated hybrids. Hybrids had mean values of 60.91 and 57.47% for digestible dry matter (DDM) and in sacco dry matter digestibility (ISDMD), respectively. Relative feed value (RFV) and dry matter intake (DMI% body weight) of hybrids 682A × 62404 and 699A × ICSR 93039 were highest among the tested genotypes. Non-fibrous carbohydrates (NFC) were highest in 682A × 62404 and 699A × ICSR 93039 hybrids. Energy value in terms of total digestible nutrients (TDN) and digestible energy (DE) was higher for 673A × GD 65 and 699A × ICSR 93039 hybrids. Net energy efficiency for maintenance (NEM), milk production and body weight gain (NEG), (NEL) was higher for 682A × 62404 and 699A × ICSR 93039 hybrids, respectively. Methane production (g/k DDM) of hybrids varied from 45.61 (679A × IS697) to 73.45 (673A × PC-6). Hybrids 673A × GD 65, 674A × JHV 12 and 699A × ICSR 93039 had higher CP, less fiber contents, more dry matter digestibility, higher palatability and net energy efficiency for different animal functions.